Talking about the pigou paradox: Socio-educational background and educational outcomes of AlmaLaurea - Floro Ernesto Caroleo; Francesco Pastore (Institute for the Study of Labor (IZA), 2011)
Italy has an immobile social structure. At the heart of this immobility is the educational system, with its high direct, but especially indirect cost, due to the extremely long time necessary to get a degree and to complete the subsequent school-to-work transition. Such cost prevents the educational system from reallocating the best opportunities to all talented young people and from altering the typical market mechanism of intergenerational transfer of human capital and social status. About ten years after the Bologna declaration and the 3+2 reform of the university system, AlmaLaurea data relative to 2008 shows a framework not much different from that of 2000. This is apparent by looking at the socio-educational background of university graduates. Parents' educational level seems to be the main determinant of the probability to get a university degree and to get it with the highest possible grade. As previous studies have also shown, the effect of the socio-educational background on children success at the university is not direct, but through the high school track. In fact, although any secondary high school gives access to the university, nonetheless lyceums provide students with far higher quality of education than technical and professional schools.
urn:nbn:de:101:1-201110263608
Keywords: H52; I23; I24; J13; J24; 330; intergenerational transfers; human capital; social status; Bologna declaration; 3+2 university reform; AlmaLaurea; Italy; Hochschulreform; Bildungschancen; Humankapital; Generationenbeziehungen; Sozialer Status; Italien